Beckman Model D2 oxygen analyzer with cord and bulb - Hesketh, Dean D. (1950)
Developed from a Linus Pauling design during WWII, the technology behind Beckman Instruments’ oxygen analyzers ended up doing such diverse jobs as monitoring astronauts’ respiration, maintaining packaged food safety, and preventing blindness in newborn babies.
Keywords: Scientific apparatus and instruments; Oxygen--Measurement; Oxygen--Analysis; Beckman Instruments, Inc.